Communicative-Pragmatic Properties of Addressing in Virtual Pedagogical Discourse: Insights from School Chats - T. G. Rabenko; E. S. Denisova; A. D. Chardyntseva (Научный диалог)
This study explores the communicative-pragmatic properties of addressing as a syntactic phenomenon manifested within virtual pedagogical discourse. The relevance ofthis topic is underscored by its integration into the scientific paradigm of discourse linguistics. The core idea of the research lies in establishing a correlational dependency among the components of the following triad: (1) the functional and goal-oriented setting of speech utterances, (2) speech strategies aimed at achieving functional communicative intentions, and (3) the material embodiment of text featuring addressing, determined by the overarching cognitive strategy of pedagogical discourse and the electronic substrate form. The empirical material consists of school chats conducted on messaging platforms such as Sferum, WhatsApp, and Telegram. This material reveals invariant characteristics inherent to addressing: its material embodiment as a word or phrase and typical functions associated with addressing. Additionally, the study identifies variable properties of addressing, determined on one hand by the institutional nature of pedagogical discourse (lexical means of addressing characteristic of Russian institutional linguoculture), and on the other hand by the electronic substrate form (the use of nicknames as forms of address, and the integration of addressing within electronic polycode texts that include, alongside verbal elements, media files and emojis).